Risk of second primary tumors in GIST survivors: A systematic review and meta-analysis. (June 2019) - Petrelli, Fausto; Tomasello, Gianluca; Barni, Sandro; Varricchio, Antonio; Costanzo, Antonio; Rampulla, Valentina; Cabiddu, Mary; Turati, Luca; Russo, Alessandro; Seghezzi, Silvia; Passalacqua, Rodolfo; Ghidini, Michele
Abstract: Introduction: Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors arising in the gastrointestinal tract. Second primary tumors (SPTs) have been reported frequently, either synchronously or during follow-up, in patients diagnosed with GISTs. Methods: We carried out an electronic search of PubMed, SCOPUS, Web of Science, EMBASE, and the Cochrane Library seeking articles investigating the incidence of SPTs in patients with concomitant GIST. All studies were evaluated for heterogeneity before meta-analysis and for publication bias. Pooled incidence rate was estimated using fixed- and random-effects models. Subsite of SPTs was also investigated. Results: A total of 32 studies met the inclusion criteria, for a total of 19, 627 patients with a diagnosis of GIST. The pooled prevalence of SPTs was 20%, with 14% and 3% being synchronous and metachronous tumors, respectively. We found a risk for several specific cancer sites, in particular gastrointestinal (5%) and genitourinary tract cancers (3%). The most frequently associated malignancies were: colorectal (17%), prostate (14%), gastric (9%), esophageal (5.5%), lung (5.4%), hepato-biliopancreatic (4.7%), breast (4.6%), lymphoma (4.4%), kidney (4.35%), and sarcomas (3.3%). Regression analyses revealed a significant positive association for all SPTs with follow-up and Miettinen risk. Conclusions: Our results indicate that 20% of patients with GIST experienced a SPT, primarily synchronously with a diagnosis of GIST. In particular, we observed an excess of incident gastrointestinal tumors. These findings have important implications for both pathologists, who should perform extensive molecular analysis of surgical non-GIST specimens in resected patients, and for oncologists, who should continue to follow up GIST patients. Highlights: GIST patients are at increased risk of second primary malignancies (SPTs). The pooled incidence rate of SPTs was 20% (mainly synchronous cancers). We found a specific risk for gastrointestinal (5%) and genitourinary cancers (3%). These findings have important implications for oncologists, who should continue to follow up GIST patients.